Assessment of serious infections in pemphigus and pemphigoid by a national registry. (10th October 2018) - Maglie, R.; Hertl, M.
Abstract : Linked article: This is a commentary on Z. Ren et al., pp. 1768–1776 in this issue. To view this article visithttps://doi.org/10.1111/jdv.14961